The Influence of Reward, Work Discipline, and Compensation on Employee Performance at PT. Metal Hitech Engineering - Kurnianti, Novia Ramadhani; Rizqi, Maulidyah Amalina (Majapahit Journal of Islamic Finance and Management, 2025)
This study aims to determine the influence of reward, work discipline, and compensation on employee performance at PT. Metal Hitech Engineering. The research employs a quantitative method with data collection conducted through questionnaires distributed to 65 respondents. Data analysis was performed using multiple linear regression, along with validity tests, reliability tests, and classical assumption tests. The results of the study indicate that reward, work discipline, and compensation have a positive and significant impact on employee performance.